Bridging Formal and Conceptual Semantics Selected papers of BRIDGE-14 - Balogh, Kata (Studies in Language and Cognition, 2017)
The articles in this volume are the outcome of the successful BRIDGE Workshop held in Düsseldorf in 2014. The workshop gathered a number of distinguished researchers from formal semantics and conceptual semantics and aimed to initiate a deeper conversation and collaboration instead of separating the two sides as competing views. The workshop provided a platform to further discuss parallelisms on specific semantic issues on the one hand and on the other hand to confront opposed claims from the two different perspectives. This volume represents a selected number of high-quality papers presented at the workshop featuring various approaches to meaning from linguistics, logic and philosophy of language. This series explores issues of mental representation, linguistic structure and representation, and their interplay. The research presented in this series is grounded in the idea explored in the Collaborative Research Center 'The structure of representations in language, cognition and science' (SFB 991) that there is a universal format for the representation of linguistic and cognitive concepts.